Effect of pulsed electron beam treatment on the release profile of chloramphenicol from polylactic acid–based polymeric scaffolds - Volokhova, Apollinariya A.; Ponomarev, D. V.; Kurzina, Irina A.; Tverdokhlebov, Sergey I. (High energy chemistry)
The paper presents the results of testing the properties of antibacterial nonwoven fibrous materials based on polylactic acid with incorporated chloramphenicol. It has been shown that exposure to a pulsed electron beam increased the rate of release of chloramphenicol into a phosphate-buffered saline medium. In this case, the amount of the substance released from treated samples was reliably greater than that with untreated samples during the five days of the experiment.